2015
DOI: 10.1021/acs.analchem.5b01431
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Raman Spectroscopic Imaging Monitors the Integral Physiologically Relevant Drug Responses in Cancer Cells

Abstract: Predictions about the cellular efficacy of drugs tested in vitro are usually based on the measured responses of a few proteins or signal transduction pathways. However, cellular proteins are highly coupled in networks, and observations of single proteins may not adequately reflect the in vivo cellular response to drugs. This might explain some large discrepancies between in vitro drug studies and drug responses observed in patients. We present a novel in vitro marker-free approach that enables detection of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 61 publications
2
57
0
2
Order By: Relevance
“…[67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging. [67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging.…”
Section: Raman Imaging Of Single Cellsmentioning
confidence: 97%
“…[67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging. [67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging.…”
Section: Raman Imaging Of Single Cellsmentioning
confidence: 97%
“…In addition, increased expression of lipogenic enzymes, such as acetyl-CoA carboxylase (ACC) and fatty acid synthase (FASN), lipid-modifying enzymes such as phosphoinositide 3-kinase (PI3K), phospholipase C (PLC) and phospholipase D (PLD) and ATP citrate lyase (ACLY), which collectively promote cholesterol biosynthesis, represent a phenotypic alteration often observed in different cancer types and frequently predict a poor prognosis in cancer patients [199204]. Furthermore, state-of-the-art analytical and imaging tools, such as electrospray ionization, matrix-assisted laser desorption/ionization, tandem mass spectrometry (MS/MS), and Raman scattering microscopy, have provided valuable lipidomic data that describe alterations in cellular lipid phenotype and fatty acid composition as well as specific spatial cellular distribution in cancer-related conditions [23, 196, 205208]. It is apparent that cancer cells display a high demand for various lipids and their excess is considered a trademark of cancer.…”
Section: Dysregulation Of Plasma Membrane Biochemical and Biophysicalmentioning
confidence: 99%
“…Vibrational spectroscopy can perform cellular imaging in a (benchtop) microscopic geometry, and can provide non‐invasive label‐free screening of, for example, nanoparticle or drug uptake, trafficking and interaction mechanisms, as well as cellular responses and toxicity , eliminating the need for multiple assays in toxicological screening and drug discovery and preclinical screening stages, by elaborate robotic high‐content analysis systems. Vibrational spectroscopy has also been demonstrated for diagnostic applications, in vivo and ex vivo, in tissue , cells and body fluids .…”
Section: Introductionmentioning
confidence: 99%
“…For realistic applications potential, however, it is important that these combinatorial signatures are characteristic of the cellular interaction and/or response pathway, and are translatable across cell lines and ultimately patient samples. Although Derenne et al demonstrated that drugs of similar mode of action have similar spectroscopic signatures using FTIR microscopy , there have been few other studies which have attempted to demonstrate consistency between spectroscopic signatures of drug interactions and cellular responses . The identification of specific spectral signatures which are common for drug mechanisms of action and cellular responses opens the perspective to a new “spectralomics” paradigm, in label‐free fingerprinting and monitoring of biological processes in cells in vitro using Raman spectroscopy, with potential applications in fundamental cytological research, pre‐clinical pharmacological development and ultimately improved individualised clinical therapeutics.…”
Section: Introductionmentioning
confidence: 99%